Prinsip Moderasi Beragama Antar Umat Beragama Dalam Kehidupan Berbangsa - Muhamad Maftuh Fauzi (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2024)
Moderation is derived from the word moderate, which means not excessive, balanced, or in the middle. In Indonesian, this term is adapted as moderasi, which according to the Great Dictionary of the Indonesian Language (KBBI), is defined as the reduction of violence or the avoidance of extremism. When combined with the word religious, forming religious moderation, it refers to an attitude of avoiding violence and extremism in religious practices.Indonesia, as a nation rich in cultural and religious diversity—including ethnicity, race, customs, language, and beliefs—possesses great potential to build a harmonious society. However, globalization and the openness of information pose challenges, especially with the spread of extreme and radical ideologies that threaten national unity. Thus, a solution is needed to serve as a filter in maintaining the essence of national life. Religious moderation offers a middle-ground approach to counter ideologies that are incompatible with the nation’s identity.Religious moderation does not mean merging or exchanging religious beliefs. Rather, it emphasizes the importance of tolerance and mutual respect in social interactions (mu’amalah) among religious communities. Within this context, every religious adherent is expected to uphold and respect social boundaries, avoid intolerance, extremism, and radicalism, and contribute to creating a peaceful coexistence for all. Therefore, religious moderation becomes a strategic solution in preserving diversity and strengthening national values within the framework of Pancasila ideology.